2018
DOI: 10.1186/s13567-018-0508-z
|View full text |Cite
|
Sign up to set email alerts
|

SeMet attenuates OTA-induced PCV2 replication promotion by inhibiting autophagy by activating the AKT/mTOR signaling pathway

Abstract: Porcine circovirus type 2 (PCV2) is recognized as the causative agent of porcine circovirus-associated diseases. PCV2 replication could be promoted by low doses of ochratoxin A (OTA) as in our previous study and selenium has been shown to attenuate PCV2 replication. However, the underlying mechanism remains unclear. The aim of the study was to investigate the effects of selenomethionine (SeMet), the major component of organic selenium, on OTA-induced PCV2 replication promotion and its potential mechanism. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…The mTOR, LC3-I, LC3-II, S6K1, p62, fibronectin, TGF-β, and β-actin antibodies used were purchased from Abcam (anti-fibronectin antibody (ab23750), rabbit polyclonal antibody [36], anti-TGF beta 1 antibody (ab92486), rabbit polyclonal antibody [37], anti-LC3-I/II antibody (ABC929, Sigma-Aldrich), rabbit polyclonal antibody [38], anti-S6K1 antibody (ab9366), rabbit polyclonal antibody [39], anti-SQSTM1/p62 antibody (ab155686), rabbit polyclonal antibody [40] and anti-mTOR antibody (ab2732), rabbit polyclonal antibody [41]). The proteins of renal tissues were extracted by RIPA lysis buffer, which was delivered by Bio Basic Inc. (Markham, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…The mTOR, LC3-I, LC3-II, S6K1, p62, fibronectin, TGF-β, and β-actin antibodies used were purchased from Abcam (anti-fibronectin antibody (ab23750), rabbit polyclonal antibody [36], anti-TGF beta 1 antibody (ab92486), rabbit polyclonal antibody [37], anti-LC3-I/II antibody (ABC929, Sigma-Aldrich), rabbit polyclonal antibody [38], anti-S6K1 antibody (ab9366), rabbit polyclonal antibody [39], anti-SQSTM1/p62 antibody (ab155686), rabbit polyclonal antibody [40] and anti-mTOR antibody (ab2732), rabbit polyclonal antibody [41]). The proteins of renal tissues were extracted by RIPA lysis buffer, which was delivered by Bio Basic Inc. (Markham, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…It is one of the smallest virus characterized so far, encoding only a capsid protein and two necessary proteins for viral replication [163]. It has been shown that selenomethionine supplementation in cell culture inhibits viral replication [164,165,166,167,168]. Furthermore, addition of H 2 O 2 or ochratoxin A that induced oxidative stress enhanced viral replication.…”
Section: Selenium Selenoproteins and Viral Replicationmentioning
confidence: 99%
“…Furthermore, addition of H 2 O 2 or ochratoxin A that induced oxidative stress enhanced viral replication. This effect was prevented by selenium supplementation [164,165,166,167,168] or by selenoproteins SELENOS and GPX1 [164,165,166,167,168]. It appears that this mechanism involved the autophagy pathway [164,165,166,167,168].…”
Section: Selenium Selenoproteins and Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mTOR, LC3-I, LC3-II, fibronectin, TGF-β and β-actin antibody used were purchased from abcam (Anti-Fibronectin antibody (ab23750), Rabbit polyclonalantibody [72], Anti-TGF beta 1 antibody (ab92486), Rabbit polyclonal antibody [73], Anti-LC3-I/II Antibody (ABC929, Sigma-Aldrich), Rabbit polyclonal antibody [74], Anti-mTOR antibody (ab2732), Rabbit polyclonal antibody [75]). The Proteins of renal tissues were extracted by RIPA lysis buffer which was delivered by Bio BASIC INC. (Marhham Ontario L3R 8T4 Canada).…”
Section: Western Blotmentioning
confidence: 99%